Habilidades técnicas y su incidencia en las secretarias administrativas del Taller Palacios periodo lectivo 2020 - 2021 - Caleño Soto, Angy Yelena (2022)
The present case study was carried out in the Palacios Workshop in the city of Guayaquil, Mapasingue Oeste, on Fifth Street and Sixth Avenue, on the technical skills of the secretarial staff, because they are important for the normal development of activities because facilitate the work of the other members of the workshop through some of its functions. For this reason, the objective of the research is to analyze the incidence of technical skills in the administrative secretaries of Taller Palacios. The methodology in the case study was made up of the type of descriptive and field research; In addition, the inductive method was used because it allowed the identification of the findings at the study site for the establishment of general conclusions. The survey technique was applied to the secretarial and administrative staff through the respective questionnaire of questions. The results obtained were that the professionals in the secretariat during the development of their activities do not usually apply adequate techniques of writing, spelling, computer science and the secretarial staff, despite fulfilling several of their roles, have deficiencies when managing the file because do not use methods that help to identify them easily. It is concluded, the functions of the secretarial staff are essential in the company, they are in charge of several activities that allow the development of activities of the administrative area or of their colleagues, by providing them with information, documents, writing reports, among others.